The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/acr2.11149
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Autoantibody Profiles for Subsetting of Native American, African American, and European American Patients With Systemic Lupus Erythematosus

Abstract: Objective Many Native American ( NA ) patients with systemic lupus erythematosus ( SLE ) do not exhibit the classical SLE autoantibody profiles of European American ( EA ) and African American ( AA ) patients with SLE . The poorer SLE disease outcomes noted in NA patients highlights a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…While the presence of autoAbs to a diverse array of nuclear and non-nuclear autoAgs has been previously noted in SLE [20,[27][28][29], here we show that this can also be seen in some ANA þ individuals lacking a SARD diagnosis. This finding indicates that a broad breach of B cell tolerance can be seen in the absence of clinical disease activity and raises the possibility that it results from the genetic polymorphisms that promote disease.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…While the presence of autoAbs to a diverse array of nuclear and non-nuclear autoAgs has been previously noted in SLE [20,[27][28][29], here we show that this can also be seen in some ANA þ individuals lacking a SARD diagnosis. This finding indicates that a broad breach of B cell tolerance can be seen in the absence of clinical disease activity and raises the possibility that it results from the genetic polymorphisms that promote disease.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have contrasted the performance of different immunoassay techniques to detect autoAbs in individuals with SARD [20,[27][28][29]. However, in general these studies have investigated their diagnostic utility in comparison with HCs, unaffected relatives and/or individuals with non-SARD musculoskeletal conditions [2,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is a huge attention to the use of autoantibodies as a predictor of disease progression in early SLE, hoping to limit the morbidity and mortality [22]. Guthridge et al concluded that studying the ANA profile may have a prognostic value in SLE patients [23]. On studying the ANA profile in our patients, we found that anti-dsDNA, anti-nucleosome, anti-histone, anti-Ro60, and anti-Ro52 autoantibodies were implicated with the highest frequency, so we evaluated the alleged role for their use as biomarkers for SLE and their relationship with disease activity and renal affection.…”
Section: Discussionmentioning
confidence: 99%
“…Major shortcomings exist in the identification and treatment of NA patients with rheumatic disease contributed by uncharacteristic clinical presentations in NA patients compared with those of White and African ancestry that define standard classification criteria (8,39). Furthermore, the heterogeneity and overlap of autoimmune disease symptomology pose significant challenges for diagnosis, treatment, research, and clinical trials.…”
Section: Discussionmentioning
confidence: 99%